Terpenoid Derivatives as Potential Trypanocidal Agents - Lozano, Esteban Sebastián (2016)
In this review we refer to a promising family of molecules in the fight against Chagas disease. Terpene derivatives are abundant in the plant Kingdom and in the last years many compounds have shown important biological activities. Diterpenes and sesquiterpene lactones have shown in vitro and in vivo trypanocidal activity and they emerge as potential antichagasic drugs. These molecules may act on these parasites by multiple mechanisms, as it has been reported. Moreover, given the chemical structure of these compounds it is feasible to modify these molecules by chemical substitution in order to optimize their action against parasites